What are they exactly? Are they similar or different? A Conceptual and Contextual Insights of Multilingualism and Plurilingualism from Indonesian EFL Classrooms - Tatipang, Devilito Prasetyo; Irwan, Anas; Syahrullah, Syahrullah; Aswat, Fajar (English Education Postgraduate Program, Universitas Negeri Manado, 2025)
This systematic literature review aims to clarify the conceptual distinctions and contextual applications of multilingualism and plurilingualism in Indonesian English as a Foreign Language (EFL) classrooms. The study addresses widespread confusion among educators and policymakers by analyzing 25 high-quality, peer-reviewed studies published between 2021 to 2025. Using rigorous selection criteria and thematic analysis, the review found that multilingualism is typically understood as the coexistence of multiple languages within societies or institutions, while plurilingualism highlights an individual's integrated and dynamic use of multiple languages. Despite Indonesia’s rich linguistic diversity, national policies and curricula have yet to fully adopt plurilingual principles, often favoring strict language separations. Classroom research reveals that language practices are more fluid, with teachers and students frequently combining languages for comprehension and engagement. However, varying teacher beliefs and insufficient training hinder the implementation of effective plurilingual pedagogy. This study underscores the need for clear, shared definitions and improved professional development to bridge the gap between theory, policy, and practice. The findings advocate for policies and teaching approaches that recognize and harness the full linguistic repertoires of learners. Ultimately, this review provides a critical foundation for advancing multilingual education in Indonesia and contributes to global discussions on language pedagogy in multilingual contexts